A droplet-based microfluidic system for high- Throughput screening of photosensitisers against microbial organisms - Cho,S; Kang,DK; Sim,S; Geier,F; Kim,JY; Chang,SI; Edel,J; Wootton,R; De,Mello A (2012)
Herein, we present a modular droplet-basecl microfluidic approach for performing liigh throughput cytotoxicity screening of photo sensitizers against microbial organisms. Multiple novel fluidic operation modalities such as large-scale chamber based light irradiation, reinjection and low voltage driven electrocoalescence are introduced. Also, photosensitiser drug cytotoxicity on E.coli cells are evaluated in microfluidic device using fluorescent viability assay indicator and compared with conventional colony forming unit counting cytotoxicity assay.